Motivasi Kerja Dan Peningkatan Jenjang Karier Terhadap Kompetensi Karyawan Mega Sejahtera - Latifah Jusdienar, Akka; Zulina Ayunani , Faras (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This article describes the independent variable. Workplace motivation and career advancement goals, along with employee competency, can be summarized as follows: Variable Work Motivation versus Competency Variable Within this context, the decisive factor (KD) The tool or method used to adjust the dependent variable’s mean value from the independent variable is usually regression analysis. Analyses of regression allow researchers to understand relationships and how certain significant changes in independent variables can affect dependent variables.In addition to it, there are other methods such as:The Analysis of Variance, or ANOVA, is used to compare two independent variables to one dependent variable.Correlation analysis: this method is used to estimate some strong correlation between two variables, yet it is not a completely silent way to identify causes. The following are some of the perhitungan techniques used: About is the value of the coefficient of determination (r) 0.605.Using the determined rumus koefisien: KD is equal to rÂ² Ã— 100%. Measuring rÂ²: \( rÂ² = 0,605 Ã— 0,605 = 0,366 \). Menghitung KD: is equal to 0,366 Ã— 100%, or 36,6%. Based on these results, it can be concluded that the work-related motivation variable affects the employee’s skill level. This statement indicates the results of a regression analysis, or a method of analysis where 36,6% of the dependent variable is explained by the independent variable that was examined. Accordingly, the model’s coefficient of determination (R2) is either 36,6% or 0,366. As an example, 63.4% of the data indicate that dependent variables are affected by unidentified or unaccounted for factors in the research model. This could mean that there is another variable anything should be considered in a more thorough study to increase the model’s accuracy in explaining the aforementioned dependent variable.A slight deviation from the mean of 36.7% to 36.6% was observed based on the deviation of rÂ². As a function of the Jenjang Karir Variable and the Karyawan Variable’s Competency, the results are manually calculated using utilizing the following rumus koefisien deterrninasi: KD = r2 x I 00%, where r is the result of a koefisien korelasi analysis with a significance level of 0.635. The results are as follows: KD is equal to r2 x 100%, 0,635 x 100%, 0,403 x 100%, or 40,3%. It is possible to deduce from these findings that the Jenjang Karir variable The statement above suggests that there is a significant relationship between the variables Work Motivation and Karyawan Competency. The regression analysis’s findings reveal a value of R of roughly 0.701, indicating a high degree of correlation between the dependent variable (Karyawan Competency) and the independent variables (Workplace Motivation and Employee Growth). In addition, the R Square (RÂ²) value of 0.492, or 49.2%, indicates that 49.2% of the Karyawan competency variable can be explained by the two independent variables mentioned above. exhibits a significant damping of 50.8%, which is the result of by unidentified supporting components in our study. In other words, both work motivation and Jenjang Karir training contribute positively and significantly to the development of employees’ skills, and this relationship is quite strong. Key words: Motivation, Work, Hard work, Skill, and Ability